Karakteristik Kimia Roti Tawar Dengan Substitusi Tepung Labu Kuning - Rosiana Ulfa; Lailianisa Wahyu Prasiwi (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2019)
In this study, researchers used pumpkin flour as a substitute for making white bread. Pumpkin, which has a high carbohydrate, protein and Vitamin A content, so it is expected that its use in white bread can increase the nutritional value of the bread produced. The study was conducted using experimental research methods, which began by making a comparison of the concentration of different pumpkin flour on the bread loaves, namely 5%, 10% and 15%. Then the process of making white bread is carried out through two stages of fermentation and the roasting process. The results showed that 10% of the white bread which was treated with substitution of pumpkin flour showed the best results. The proximate test shows that the content of vitamin A from 10% substituted white bread flour is 0, 0805%. The protein content is 7.33% and fat content is 1.31%. These results indicate that the addition of pumpkin flour significantly increases the nutritional content of the bread produced.